2022
DOI: 10.55519/jamc-03-10167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Topical 0.1% Adapalene Gel Versus Cryotherapy Treatment in Patients With Plantar Warts

Abstract: Background:  Plantar wart is a common viral infection of the plantar surface of the foot. Multiple treatment modalities are available but there is no definitive management option. The aim of this study is to compare topical adapalene gel 0.1% with cryotherapy in patients presenting with plantar warts in terms of time taken for complete clearance of the lesions. Methods: The study was conducted at the department of Dermatology, PNS Shifa Hospital, Karachi from 28th April to 28th October 2020. Eighty-four patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Men and women made up 65% and 35% of the patient population, respectively (Table 1). The few studies from Asia, such as those from Singapore, that have examined male and female dengue incidence have tended to find greater male incidence 16–18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men and women made up 65% and 35% of the patient population, respectively (Table 1). The few studies from Asia, such as those from Singapore, that have examined male and female dengue incidence have tended to find greater male incidence 16–18 …”
Section: Discussionmentioning
confidence: 99%
“…The few studies from Asia, such as those from Singapore, that have examined male and female dengue incidence have tended to find greater male incidence. [16][17][18] In our study, the common general symptoms reported are fever (n = 152), headache (n = 136), myalgia (n = 104), arthralgia (n = 94), retro-orbital pain (n = 94), and diarrhea (n = 50) respectively. Another study in Asia reported severe fever (100%), body aches (93.1%), skin rashes (26%), nose and/or mouth bleeding (5.63%), and an enlarged liver (43.96%) as the predominant clinical features among dengue patients, which are similar to our study findings.…”
Section: Clinical Course and Serotypementioning
confidence: 99%